2021
DOI: 10.1002/emp2.12427
|View full text |Cite
|
Sign up to set email alerts
|

False negative point‐of‐care urine pregnancy tests in an urban academic emergency department: a retrospective cohort study

Abstract: Study objective:To determine the prevalence of false negative point-of-care (POC) urine pregnancy tests among emergency department (ED) patients and among those with abdominal pain or vaginal bleeding. Methods:We identified all female patients, ages 14-50 years without prior hysterectomy who had a negative POC urine pregnancy test (beta subunit of human chorionic gonadotropin [β-hCG]) performed by trained clinical staff in the ED between September 1, 2017 and December 31, 2018, as well as a subgroup we defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Using pregnancy tests as reference, wherein a negative test ideally represents a 0% chance of pregnancy, a recent retrospective study at a large urban American academic medical center found a false-negative rate of just 1.6%, which was a reported cause for concern. 14 Although our results agree with consensus in the literature reporting increased cEEG seizure detection rates compared to non-cEEG, we did not take the typical route of describing increased cEEG detections; rather, we adopted a unique approach of estimating the number of seizures left behind when cEEG is not used, allowing for more direct risk assessments of not using cEEG. To assist QI initiatives elsewhere, other centers may calculate their own “seizure miss rates” using our custom-coded MATLAB residual risk estimator to assess their own institutional risk tolerance based on existing 2HELPS2B criteria and to justify potential deviations below or above the suggested 5% benchmark.…”
Section: Discussionsupporting
confidence: 81%
“…Using pregnancy tests as reference, wherein a negative test ideally represents a 0% chance of pregnancy, a recent retrospective study at a large urban American academic medical center found a false-negative rate of just 1.6%, which was a reported cause for concern. 14 Although our results agree with consensus in the literature reporting increased cEEG seizure detection rates compared to non-cEEG, we did not take the typical route of describing increased cEEG detections; rather, we adopted a unique approach of estimating the number of seizures left behind when cEEG is not used, allowing for more direct risk assessments of not using cEEG. To assist QI initiatives elsewhere, other centers may calculate their own “seizure miss rates” using our custom-coded MATLAB residual risk estimator to assess their own institutional risk tolerance based on existing 2HELPS2B criteria and to justify potential deviations below or above the suggested 5% benchmark.…”
Section: Discussionsupporting
confidence: 81%
“…To use an example from daily life, people awaiting the results of a medical diagnostic test would not be happy if it could only detect a life-changing condition 80% of the time! Accordingly, some medical tests have very low false-negative rates (e.g., some pregnancy tests have only a 1% false-negative rate with others no higher than 5%; Bhandari, 2019 ; Kleinschmidt et al, 2021 ). Regardless of the exact approach one uses, however, it is important to justify trade-offs involved in adopting any power criterion, as with any particular value of α ( Lakens, Adolfi, et al, 2018 ).…”
Section: Sample Size Determination Methodsmentioning
confidence: 99%
“…found an overall false negative rate of ∼1.6% out of over 11,000 patient visits. Interestingly in a subset of patients with “high‐risk complaints,” including pain, cramping, pelvic pain/cramping, and vaginal bleeding, the false negative rate was ∼3.6% 5 . The authors reported 12 ectopic pregnancies in patients with negative UPT with 83% of cases occurring in the high‐risk group.…”
Section: “What Can We Hang Our Hat On?”mentioning
confidence: 99%
“…Interestingly in a subset of patients with “high‐risk complaints,” including pain, cramping, pelvic pain/cramping, and vaginal bleeding, the false negative rate was ∼3.6%. 5 The authors reported 12 ectopic pregnancies in patients with negative UPT with 83% of cases occurring in the high‐risk group. Similarly, the authors reported that ∼75% of all “abnormal pregnancies” occurred in this high‐risk group.…”
Section: “ What Can We Hang Our Hat On? ”mentioning
confidence: 99%